The Influence of Public Service Motivation on the Performance of Batu Mila Village Officials, Maiwa District, Enrekang Regency - Nurlaila Sari Jamaluddin; Andi Uceg; Sapri Sapri (Universitas Muhammadiyah Enrekang, 2024)
The aim of this research is to determine Public Service Motivation and Performance of BatuMila Village Officials as well as the factors thet influence Public Service Motivation on thePerformance of Village Officials in Batu Mila Village, Maiwa District, Enrekang Regency. There were425 families in the study population, and 43 people were sampled. Simple random sampling is thesampling method used. This kind of research is carried out using numbers. To collect data for this study,questionnaires, interviews, and literature reviews were used. By using a Likert scale and the SPSSprogram, the data analysis technique used is basic linear regression analysis, validity and reliability. Theresults showed that there is an influence between public service motivation and the performance of BatuMila village officials is categorized as “significantly influential”, from the ANOVA test, the F countobtained was 5.355 with a significance level of 0.026. the calculated t value (2.314) > t tabel (2.019)means that public service motivation has a significant effect on the performance of the Batu MilaVillage device by 11,5%.